Improved cardiovascular outcomes following temporal advances in lipid-lowering therapy in a genetically-characterised cohort of familial hypercholesterolaemia homozygotes. Issue 1 (November 2015) - Thompson, Gilbert R.; Seed, Mary; Naoumova, Rossi P.; Neuwirth, Clare; Walji, Shahenaz; Aitman, Timothy J.; Scott, James; Myant, Nicolas B.; Soutar, Anne K.
Abstract Background and aims There is a paucity of data concerning the influence of lipid-lowering therapy on cardiovascular (CV) outcomes in patients with homozygous familial hypercholesterolaemia (FH). To redress this a retrospective analysis was undertaken of the demographic features, lipid levels, low density lipoprotein receptor and Autosomal Recessive Hypercholesterolaemia gene mutations, CV outcomes and vital status of 44 FH homozygotes referred to a single centre in the UK between 1964 and 2014. Methods Data were obtained from past publications, case records and death certificates. Differences in categorical and continuous variables between living and dead patients were analysed using Fisher's exact test and an independent t-test respectively. Results During the 50 years covered by this survey 13 patients have died, 30 are still alive and 1 was lost to follow up. The mean age of Alive patients was 32.6 ± 11.5 versus 28.3 ± 14.9 years in Dead ones (P = 0.31) and they were born 18 years later (P = 0.0001). Pre-treatment serum total cholesterol (TC) was similar in Alive and Dead (20.2 ± 5.1 v 21.3 ± 4.4 mmol/l, P = 0.52) but on-treatment TC was lower in Alive than Dead (8.1 ± 2.8 v 14.5 ± 6.0 mmol/l, P = 0.0001) and CV adverse events were far less frequent (eg aortic stenosis, 33% v 77%, P = 0.02). Conclusions The lower on-treatment TC and fewer CV adverse events in FH homozygotes still living reflect advances in apheresis and drug therapy since the 1990s. Further improvements in prognosis can be expected with the impending introduction of novel lipid-lowering agents.